การวางแผนการตอบสนองความเสี่ยงโดยใช้การประกันภัยก่อสร้าง - วินิจ ร่วมพงษ์พัฒนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The construction insurance is a method of risk response in the form of risk transfer. Construction insurance contracts (or insurance policies) have unique, complex, and elaborate provisions. Besides, they are often overlooked by civil engineers who manage construction projects. In general, terms and conditions in this type of contract are drafted by the insurance company or the insurance broker that might not completely understand construction works. This may lead to an insurance policy that is not as desired by the project owner or the contractor. Additionally, it may also cause various problems concerning contract administration such as the claim rejected by the insurer. This thesis investigates important issues in risk response by using construction insurances. It began with analyzing and summarizing detailed steps of construction insurance acquisition process. For risk management in construction insurance policy, 29 risk factors in construction insurance acquisition and management were identified and classified into four categories. This analysis was based on literature review and interviews with 44 experts from 22 construction firms, who have experience in insurance acquisition and management in Thailand. This thesis delineates details of important provisions of construction insurance policies. Finally, this thesis summarizes important issues and considerations which all parties should realize during construction insurance acquisition and management. Construction project owners and contractors can apply the findings from this thesis to prepare and administer their construction insurance contracts appropriately with the maximum efficacy.